QTL mapping for Caenorhabditis elegans survivorship in response to Escherichia coli and Stenotrophomonas maltophilia - Wang, Ziyi (Kansas State University, 2016)
Caenorhabditis elegans are free-living bacterivorous nematodes that naturally consume bacteria as food source. As an excellent genetic model, C. elegans has proven to be a successful system to study innate immune responses to human pathogens, which resulted in identification of many evolutionarily conserved defense pathways. Most of these studies examined innate immune pathway mutants in a single genetic background in response to monoculture of human pathogens that worms might not necessarily encounter in the wild. While this has led to the successful genetic dissection of these defense pathways, in order to fully understand their biological functions, the relevant ecological and evolutionary context needs to be taken into account. The bacterial environment C. elegans naturally encounter is likely to be highly heterogeneous. While many bacteria are mainly considered as dietary resource for worms, some could be potential pathogens. Worms thus constantly face the challenge to defend against the pathogens mixed in the food. Stenotrophomonas maltophilia is one such bacterium. S. maltophilia is a ubiquitous bacterium that has been found associated with native nematodes. But it can also cause nosocomial infections in human, especially in immune-compromised individuals. Due to its natural resistance to multiple antibiotics, it has been emerging as an opportunistic human pathogen. Our lab isolated a S. maltophilia strain, JCMS, which was found being pathogenic to C. elegans. Both C. elegans strains, N2 (Bristol, England) and CB4856 (Hawaii), showed decreased survivorship when fed on S. maltophilia JCMS compared to E. coli OP50. However, more interestingly, the specific responses towards bacteria are different between strains. This indicates that survivorship of C. elegans is determined by not only genetic and environmental factors, but also genotype by environment (G×E) interactions (GEI). In order to identify the underlying genetic basis, we mapped quantitative trait loci (QTL) in a N2×CB4856 recombinant inbred panel for the survivorship in response to E. coli OP50 and S. maltophilia JCMS.
Keywords: Caenorhabditis elegans; Quantitative Trait Loci; QTL mapping; Genotype by environment interaction